PERANAN ORGANISASI REMAJA MASJID DALAM MENGATASI KENAKALAN REMAJA: STUDI DI KELURAHAN TANAH SERIBU KOTA BINJAI - Nasution, Muhammad Amin (Hukum tata Negara/Siyasah, 2022)
Currently, youth organizations in mosques are not the main choice for youth activities. Teenagers are often engrossed in activities that have nothing to do with mosque youth organizations. In the end, their activities tend to be juvenile delinquency. In addition to the community and the role of parents, mosque youth organizations also have a crucial role in overcoming juvenile delinquency. The focus of this research is the role of mosque youth organizations in the Tanah Seribu Village, Binjai City. This research uses a type of quantitative-based qualitative research, where data is taken directly from interested parties which are then processed to be fully described. The results of this study indicate that teenagers in the Tanah Seribu Village, Binjai City who do not participate in activities in mosque youth organizations tend to be naughty and even harm the surrounding community. The role of youth in the mosque until now is very much needed. In addition to a persuasive approach which incidentally is fellow youth, their role is also aimed at preventing youth who are not members of a mosque youth organization from committing naughty acts which of course lead to them getting worse.